CSR Disclosures: Role and Relationship to Accounting Conservatism in Improving Earnings of Quality - Noor, Aspyan; Lahaya, Ibnu Abni; Kurniawan, Indra Suyoto; Najat, Shally; Hafidz, Syifa Azzahra (Jurnal Keuangan dan Perbankan, 2021)
Several research issues argue, in general, companies that focus and are oriented towards the implementation of Corporate Social Responsibility (CSR). It is relative to accounting conservatism to suppress information asymmetry and/or managerial opportunism to provide higher quality earnings information as a reflection of the actual condition of the company. This study was conducted to look at the effect of CSR disclosure on earnings quality by adding accounting conservatism as a mediating variable. This study uses path analysis techniques in 90 manufacturing companies for an observation period of 4 (four) periods from 2016 to 2019. The results of this study indicate that CSR disclosure influences Accounting Conservatism. Then, CSR affects earnings quality. Furthermore, earnings quality is influenced by accounting conservatism, and finally, CSR disclosure does not affect earnings quality according to accounting conservatism. CSR Disclosure, Accounting Conservatism, Earnings Quality.DOI: 10.26905/jkdp.v25i3.5030